Crystal structure and Hirshfeld surface analysis of the organic–inorganic hybrid compound tris(2-iodoethylammonium) hexaiodidobismuthate(III) - Olesia I. Kucheriv; Valeriia M. Ovdenko; Iryna S. Kuzevanova; Irina A. Golenya; Il'ya A. Gural'skiy (Acta Crystallographica Section E: Crystallographic Communications)
The asymmetric unit of the title organic–inorganic salt, (IC2H4NH3)3[BiI6], consists of a [BiI6]3− octahedron and three 2-iodoethylammonium cations. The octahedra do not interact with each other, and the supramolecular arrangement is ensured by an intricate network of N—H...I hydrogen bonds between cations and anions. In addition, a weak I...I interaction between an organic cation and the coordination octahedron is present in the crystal structure. Hirshfeld surface analysis revealed that the most important contributions to the crystal packing are from H...I (72.3%) and I...I (11.3%) interactions.